EVALUASI PROGRAM PENCEGAHAN DAN PENANGGULANGAN TUBERKULOSIS DI WILAYAH KERJA PUSKESMAS TERISI KABUPATEN INDRAMAYU - Widyastuti, Setyo Dwi (JURNAL KESEHATAN INDRA HUSADA, 2023)
Tuberculosis is an infectious disease caused by infectionMycobacterium tuberculosis bacteria. Discovery of tuberculosis cases in the DistrictIndramayu from 2019 to 2021 shows a declining trend for threeyear of observation, but the TB cure rate in 2019 was 91.9%decreased when compared to 2020 which was reported as many as70.8%. In 2021 the number of TB cases in Indramayu Regency will be foundas many as 1,647 cases. The implementation of the P2TB program has several obstaclesincluding TB program holders who concurrently serve, reporting fromHealth Center to the Health Service which is not optimal, counseling from the partiesPuskesmas related to the TB program are not optimally carried out, and SupervisorsTaking Medicines (PMO) that are not functioning optimally. This research methodusing qualitative research methods with a case study approach.There were 8 informants in this research. The results of this study showthat health promotion activities are still not optimal. Human Resourcesaccording to standards, the availability of logistics and funds is sufficient. Recordingand reporting is still hampered by the network and mastery of health workersto information systems. The participation of the community has not been carried out thoroughlyoptimal. In the process of implementing the P2TB program, it shows thatProgram planning at the Puskesmas is good. Implementation of the P2TB Programcarried out by visiting contacts at home with TB sufferers and visitsindependent practice, and the supervision carried out is optimal. Achievement resultsThis shows that the detection of sufferers has not reached the target set.In 2021 the set target is 175, the achievements are only51 cases found.